2013
DOI: 10.1007/s10517-013-1979-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Macrophages in BCG Granulomas in Different Compartments of the Mononuclear Phagocyte System

Abstract: We studied in vitro morphological and functional properties of macrophages associated with their M1 and M2 polarization in different mononuclear phagocyte compartments during BCG-induced granuloma formation, namely expression patterns of cytokines IL-1α, GM-CSF, TNF-α, and clusters of differentiation CD36 and CD16/32. We showed the mosaic pattern of macrophage polarization in BCG granulomatosis manifested by simultaneous formation of different macrophage subpopulations with M1 and M2 phenotypes in the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…We have previously shown that proportions ofILla-, TNF-a-, and GM-CSF-expressing macrophages from BCG granulomas, explanted in cultures one month after BCG vaccine infection, was more than lO-fold higher than the proportion of macrophages expressing the same cytokines and obtained from intact animals (11,16). The approximate two-fold decrease of these indicators was seen three months after infection.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We have previously shown that proportions ofILla-, TNF-a-, and GM-CSF-expressing macrophages from BCG granulomas, explanted in cultures one month after BCG vaccine infection, was more than lO-fold higher than the proportion of macrophages expressing the same cytokines and obtained from intact animals (11,16). The approximate two-fold decrease of these indicators was seen three months after infection.…”
Section: Resultsmentioning
confidence: 93%
“…The approximate two-fold decrease of these indicators was seen three months after infection. It was found that the proportions of BCG-infected mice splenic macrophages expressing IL-la, TNF-a and GM-CSF was several-fold higher than that of controls but significantly lower than in populations of macrophages from BCG granulomas (11,16). In this regard, it seemed interesting to elucidate the role of the investigated cytokines in antimycobacterial activity of macrophages of BCG granulomas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, carbon from various sugars and fatty acids are extracted by Mtb in host cells via its major enzymes, such as the polyphosphate glucokinase, isocitrate lyases (ICL1 and ICL2), and the phosphoenolpyruvate carboxykinase ( 37 39 ). Mtb favors the differentiation of macrophages toward M2 subtype ( 40 ). By contrast, it impairs the formation of M1 macrophages.…”
Section: Evasion Strategies Adopted By Mtb To Counmentioning
confidence: 99%
“…The expressions of different cytokine genes were examined for studying the macrophage polarization (Martinez and Gordon, 2014;Donates, 2014). There were some published articles about different aspects of BCG vaccine like its effect on classical macrophage polarization (Iqbal and Hussain, 2014;Oliveira, 2013;Lardone et al, 2013;Arkhipov et al, 2013;Nadeev et al, 2008;Potapova and Shkurupiy, 2008) and the effect of hydatid cyst fluid on alternatively activation of macrophages (Amri and Touil-Boukoffa, 2013). The purpose of this study was to investigate the gene expression system of TNFα and IFNγ for the group which was exposed to BCG particles and also, studying the expression of IL4 and TGFβ genes in macrophages which were exposed to fertile hydatid cyst fluid.…”
Section: Introductionmentioning
confidence: 99%